Redescription of the percoid fish Symphysanodon andersoni Kotthaus (Symphysanodontidae) from the northwestern Indian Ocean, based on the holotype and the second known specimen - Anderson, William D., Jr.; Chesalin, Mikhail V.; Jawad, Laith A.; Shajibi, Said R. Al (Zootaxa, 2015)
Symphysanodon andersoni was described in 1974 from a single specimen collected southwest of Socotra Island, near the entrance to the Gulf of Aden. A more recent report (2003) of its capture in the Gulf of Kutch, Arabian Sea, was based on a misidentification. The second known specimen of the Bucktoothed Slopefish, S. andersoni, (at 204 mm SL the largest known specimen of the genus Symphysanodon) was collected off the south coast of Oman, Arabian Sea, in April 2014. Symphysanodon andersoni is distinguishable from its congeners by number of tubed scales in the lateral line, 60 to 65 versus 42 to 59 in the other species of the genus. In view of the fact that S. andersoni is poorly known, we redescribe it based on the holotype and the new specimen collected off Oman and provide the first color photograph of the species.